Normalization of HE-stained histological images using cycle consistent generative adversarial networks [dataset] - Runz, Marlen; Weis, Cleo-Aron Thias (Universität, 2021)
Here we provide the data sets supporting the experiments in our publication Normalization of HE-Stained Histological Images using Cycle Consistent ...